Analisis Penerapan Prinsip-Prinsip Syari’ah pada Wisma Pondowo Syari’ah - Muhammad Iqbal; Riyan Pradesyah (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The more the Islamic economy develops in Indonesia, the more sharia-based businesses, such as sharia lodging that implements sharia principles in all its activities both planning and implementation and utilization. The formulation of the problem in this research is how application of sharia principles to Wisma Pondowo Syari’ah. Study this aims to determine the application of sharia principles at Wisma Pondowo Syari’ah. This study uses descriptive research with data analysis qualitative, problem solving procedures by describing, describing the state of the object at the present time based on the facts that appear and as it is with observation techniques, interviews, and documentation. The results of the research show that the principles of sharia have implemented including the hotel rules and policies on the whole. However, there are still drawbacks when it comes to implementing sharia principles such as the provision of prayer rooms (musholla) and clothing employees who are still not in accordance with sharia principles. Keywords: Sharia Business, Wisma Pondowo Sharia, Sharia Principles